2015
DOI: 10.1088/0957-4484/26/24/245202
|View full text |Cite
|
Sign up to set email alerts
|

Reducing error rates in straintronic multiferroic nanomagnetic logic by pulse shaping

Abstract: Dipole-coupled nanomagnetic logic (NML), where nanomagnets (NMs) with bistable magnetization states act as binary switches and information is transferred between them via dipole-coupling and Bennett clocking, is a potential replacement for conventional transistor logic since magnets dissipate less energy than transistors when they switch in a logic circuit. Magnets are also 'non-volatile' and hence can store the results of a computation after the computation is over, thereby doubling as both logic and memory-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 41 publications
0
27
0
Order By: Relevance
“…The latter are more energy-efficient, but also more error-prone. Theoretical estimates of switching errors in magneto-elastic switching (straintronics) range from 10 -3 [8] to as low as 10 -8 [9], but experiments show a much larger error probability exceeding 0.1 [10,11]. Recently, we showed that this large difference between theory and experiments accrues from the fact that real nanomagnets used in experiments invariably have structural defects and they exacerbate the switching error [12].…”
Section: Introductionmentioning
confidence: 94%
“…The latter are more energy-efficient, but also more error-prone. Theoretical estimates of switching errors in magneto-elastic switching (straintronics) range from 10 -3 [8] to as low as 10 -8 [9], but experiments show a much larger error probability exceeding 0.1 [10,11]. Recently, we showed that this large difference between theory and experiments accrues from the fact that real nanomagnets used in experiments invariably have structural defects and they exacerbate the switching error [12].…”
Section: Introductionmentioning
confidence: 94%
“…The effect of thermal noise is incorporated by adding an equivalent field   thermal Ht to the total effective field [11,12,15,[20][21][22]:…”
Section:  mentioning
confidence: 99%
“…The Achilles' heel of strain-clocked DC-NML is its poor reliability due to high switching error rates at room temperature [10][11][12][13][14]. In this paper, we explore ways of mitigating the poor reliability, particularly through the use of appropriate geometry of the nanomagnets, and identify the metrics that have to be sacrificed to attain increased robustness.…”
Section: Introductionmentioning
confidence: 99%
“…Due to its crucial importance, the effect of thermal noise on the dynamic behavior of the magnetization in a nanomagnet has been the subject of study in the literature. [24][25][26][27] A general study of the dynamics in a single domain magnet under Langevin thermal noise has been published previously, 24 providing a comprehensive statistical analysis on the magnetization dynamics with and without the effect of external magnetic field. Analysis of the dynamics in strain-induced multiferroics has also been the subject of study recently.…”
Section: Introductionmentioning
confidence: 99%